Productivity and GDP: international evidence of persistence and trends over 130 years of data - Gil-Alana, Luis A.; Solarin, Sakiru Adebola; Balcilar, Mehmet; Gupta, Rangan (Physica-Verlag Gmbh & Co, 2023)
The degree of persistence of the real gross domestic product per capita, total factor productivity and labour productivity has been examined in a group of 23 developed and developing nations, as well as the overall Euro Area, by evaluating the order of integration of the macroeconomic series over the annual period from 1890 to 2019. As against the conventional use of using integer degrees of differentiation (i.e. 0 for stationary processes and 1 in case of unit roots), fractional values have been utilized. The empirical findings provide evidence for mean reversion in both total factor productivity and the real gross domestic product per capita in Chile, Germany, the Netherlands and New Zealand. The results further suggest that mean reversion only occurs in labour productivity of Australia. The non-linearity analysis shows that non-linearity is also present in the majority of the series. The policy implications of the results are enumerated in the body of the paper.
Keywords: Productivity; GDP; Persistence; Long memory; Fractional integration